Anti-Gender Mobilizations in Europe and the Feminist Response Productive Resistance - Smrdelj, Rok.; Kuhar, Roman; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This book provides a comprehensive mapping of anti-gender mobilizations in Italy, Slovenia, France, Spain, Turkey, Poland, Greece, and Denmark. In recent years, Europe has witnessed the rise and consolidation of these mobilizations, posing significant challenges to progress in equality politics. While analyzing the key actors, strategies, and discourses driving these movements, the book also shifts its focus to feminist and LGBT+ resistance. Drawing on interviews with activists from eight European countries, it identifies key opposition strategies that increasingly reflect productive resistance. By examining these evolving forms of activism, the book sheds light on the threats posed by anti-gender mobilizations and the innovative responses that sustain feminist and LGBT+ movements in today$1 (Bs struggles. It will be of interest to researchers and students in gender studies, feminist studies, political sociology, and comparative politics. Rok Smrdelj is an Assistant Professor of Sociology at the University of Ljubljana, Slovenia. Roman Kuhar is Professor of Sociology at the University of Ljubljana, Slovenia.s
The Rise of Anti-Gender Mobilizations -- Contentious Gender Politics in Italy: Feminist Responses to Anti-Gender Mobilizations -- Navigating Antagonism: Feminist and LGBT+ Responses to Slovenian Anti-Gender Mobilizations -- The Battle of Concepts: French Feminist Mobilizations Against the Far Right$1 (Bs Appropriation of the Feminist Legacy -- From Confrontation to Avoidance: Feminist Responses to Anti-Gender Mobilization in Spain -- Anti-Feminist and Anti-Gender Coalitions and Feminist Resilience in Turkey -- Not Just Ranting in the Streets, but Also Concrete Actions: Polish Feminist and LGBT+ Responses to Anti-Gender Politics -- Patriarchal Backlash and Feminist Responses in Greece Today -- (3z(BSo Common to Score Cheap Points on Being an Antifeminist(3y(B: The Rise of Antifeminist and Anti-Gender Mobilizations in Denmark and the Feminist Response -- Productive Resistance.s
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sex; Identity politics; Feminism; Feminist theory; Comparative government; Europe -- Politics and government; Gender Studies; Politics and Gender; Feminism and Feminist Theory; Comparative Politics; European Politics